Hygiene knowledge, attitudes and practices among dairy value chain actors in Assam, north-east India and the impact of a training intervention - Lindahl, Johanna F.; Deka, Ram Pratim; Asse, Rainer; Lapar, Ma. Lucila; Grace, Delia (Informa UK Limited, 2018)
Background: Food-borne diseases are contributing to health burdens globally, especially in developing countries. In India, milk production is important for nutrition security, but milk products are prone to contamination with pathogens. In Assam, a state in Northeast India, a novel hygiene intervention was conducted in 2009–2011, and the knowledge, attitudes and practices among milk producers, milk traders and sweet makers were assessed.Methods: The first survey was conducted in 2009 and included 405 producers, 175 traders and 220 sweet makers from 4 districts. The second survey was conducted in 2012 with 161 producers and 226 traders from 2 districts, both trained and untrained participants. In addition to questionnaires, observations on hygiene were done and samples were analysed for Escherichia coli. Results: In 2009 only 13.0%, 9.1%, and 33.1% of producers, traders and sweet makers respectively believed diseases could be transmitted by milk. There were significant improvements in knowledge after training among both traders and producers. The proportion of samples containing added water decreased from 2009 to 2012. Although knowledge had increased, all samples tested contained E. coli. Conclusion: This study shows a need to increase knowledge about milk-borne diseases and hygiene, and the positive effect of a training intervention.